If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 33 = 9 Reorder the terms: 33 + -6x = 9 Solving 33 + -6x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -6x = 9 + -33 Combine like terms: 33 + -33 = 0 0 + -6x = 9 + -33 -6x = 9 + -33 Combine like terms: 9 + -33 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| -3-7=3x+7x-12x | | 7a-a=0 | | 6x-(4x+5)=4x-27 | | 80-(7x+8)=7(x+6)+x | | -w=-18 | | 0.3(x+100)+1.1x=79 | | 6y+7x=280 | | 4x+9-7x=18-14x+11x-9 | | -7/2(2b+4)+5(4b+2)=0 | | 17+6=3x | | -4x+10=-3(2x+2) | | 660/x=25/3 | | 0.4(x-4)=4.0 | | (x-3+9i)(x-3-9i)=0 | | 3y+8x=12 | | X*.03=28 | | 1/5(3x-4)=2/5 | | 1-x+4x+17=3x | | h([-3])=2x+4 | | y=0+(-4) | | 6x^2+12x=4 | | 4=-y | | 2x+6=8x-31 | | .85=200 | | 3x-12+15=2x+10 | | 5y-9+y+36=8y+30-5y | | 0.8=200 | | 13x+7=5x+7 | | 4(lnx)-lnx^4=0 | | 7x+8=7x+3 | | 0.25=10 | | 5x+3=-3+3x+22 |